Science teaching: perceptions, attitudes and instructional practices - Phang Yeen Cheng, Talib Othman, Othman Azraai, (Universiti Pendidikan Sultan Idris, 2016)
Science teaching: perceptions, attitudes and instructional practices by Phang Yeen Cheng, Talib Othman, Othman Azraai,